ANALISIS MOTIVASI KERJA DALAM MENINGKATKAN KINERJA KARYAWAN PADA RESTORAN NUR CORNER – JAKARTA SELATAN - Aditya Ihza Mahendra; Theobaldus Boro Tura (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze work motivation in improving employee performance at Nur Corner Restaurant, Jakarta. The background of this research is based on several issues found related to employee discipline, work initiative, and the effectiveness of motivation provided by management, which affect employee performance. Therefore, an in-depth study is needed to understand how work motivation is implemented and its impact on improving employee performance. The research method used is a qualitative method with a case study approach. Data collection techniques include observation, interviews, and documentation. The informants in this study consist of the store supervisor, shift leader, greeter, staff kitchen, barista, waiters of Nur Corner Restaurant Jakarta. The data analysis technique uses an interactive model, including data reduction, data display, and conclusion drawing. The results show that work motivation plays an important role in improving employee performance. The forms of motivation provided include direct supervision, guidance, and harmonious working relationships. However, there are several inhibiting factors such as suboptimal compensation systems, lack of recognition for high-performing employees, and a dominant supervision pattern. Meanwhile, supporting factors include a conducive work environment and good relationships among employees. The conclusion of this study is that work motivation has a significant influence on improving employee performance, especially in terms of discipline, responsibility, and work quality. Therefore, it is recommended that the management of Nur Corner Restaurant Jakarta improve the reward system, enhance leadership approaches, and develop more structured motivational strategies to optimize employee performance. Thus, work motivation has an important role in improving employee performance at Nur Corner Restaurant Jakarta.